How to Save a Failing Fellowship: Drexel Infectious Disease Improvement in ACGME Fellow Survey Results. (4th October 2017) - Schultz, Sara; Momplaisir, Florence; Althoff, Amy; Szep, Zsofia; Lee, Dong Heun
Abstract: Background: Less than two-thirds of Infectious Disease Fellowship programs filled in the 2017 All-In match. The pressure to fill ID training programs with desirable candidates increases the need for programs to become both more robust and more attractive. Here, we describe the two-year experience of improving our program in each of the ACGME Fellow Survey categories. Methods: After low scores on the 2015 ACGME Fellow Survey, faculty at Drexel University Division of Infectious Diseases in Philadelphia, PA completed an overhaul of the ID fellowship program over a two-year period. We reduced the number of weekend calls and restructured clinical time to make appreciable changes to duty hours and fellow workload. We initiated a culture shift in order to increase collegiality and respect, faculty conference attendance, and research mentorship. We revitalized our conference schedule to incorporate more didactic lectures by faculty, featuring a yearlong Core Lecture Series, an interactive board review curriculum, and a new ID Grand Rounds speaker series. We provided our fellows educational resources including tablets, access to an online ID Board Review course, and protected time and funding to present their research at local, regional and national meetings. To quantify our efforts, we analyzed our ACGME Fellow Survey data for 2015–2017. Results: Over a two-year period, we made improvements across all six of the ACGME survey categories. The ACGME reports data as ÒTotal Percentage Compliance, Ó an average of fellow responses in each category measuring satisfaction on a one-to-five scale (with five being the highest). In the ÒFacultyÓ category, the 2015 Fellow Survey had a Total Percentage Compliance of 19.6. This improved to 66.7% in 2016, and 96.7% in 2017. In the ÒEducational ContentÓ category, the 2015 Fellow Survey had a Total Compliance of 37.5% in 2015, 68.8% in 2016, and 93.8% in 2017. See Figure 1. Conclusion: Although changing institutional culture is a slow process, we found that by making a series of changes to the structure of the program, collegiality between attendings and fellows, the content of conferences, and the educational resources available to fellows, we were able to transform our fellows' attitudes toward the Drexel ID Fellowship Program. Disclosures: All authors: No reported disclosures.